PENGARUH KINERJA ESG DAN KEBERAGAMAN DEWAN KOMISARIS TERHADAP PENGHINDARAN PAJAK (Studi Empiris pada Perusahaan sektor Manufaktur dan Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Dody Yusuf; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of Environmental, Social and Governance (ESG) performance and board of commissioners diversity including gender diversity, expertise diversity, age diversity, and nationality diversity on corporate tax avoidance. In addition, this study incorporates firm size, leverage, and profitability as control variables. The research population consists of all manufacturing and energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. A total of 158 firm-year observations were selected using a non-probability sampling method with a purposive sampling technique. This quantitative study employs panel data regression analysis as the statistical method. Data processing and hypothesis testing were conducted using Eviews version 13.The results indicate that board expertise diversity has a positive and significant effect on tax avoidance, suggesting that a more diverse composition of expertise among board members is associated with higher levels of tax avoidance. However, Environmental, Social and Governance (ESG) performance, board gender diversity, board age diversity, and board nationality diversity do not have a significant effect on tax avoidance.